Measuring aspects of self in dementia and investigating the validity of a self-compassion scale - Baggaley, Jessica Amber (2023)
This portfolio thesis consists of three parts. Part one is a systematic literature review, part two is an empirical paper and part three forms the accompanying appendices. Overall, they aim to evaluate and to add to the existing literature in relation to measuring specific aspects of self with people living with dementia. Part One: A systematic literature review that investigated what aspects of self have been measured using self-report instruments in evaluating psychosocial interventions for people with dementia. A narrative synthesis was conducted with 24 studies and included a variety of psychosocial interventions. The review identified seven aspects of self, which were measured using a range of self-report instruments, however the effectiveness of the interventions for these aspects of self were mixed. Limitations and methodological quality of the studies are discussed, alongside clinical implications and future considerations for research. Part Two: An empirical study that investigated the validity, reliability, and factor structure of the SCS-SF for people with dementia, as well as exploring correlations with well-being and demographic differences in self-compassion. The SCS-SF subscale intercorrelations and correlational analyses with measures of well-being, self-esteem and depression were investigated to assess convergent and discriminant validity of the SCS-SF in dementia. Exploratory Factor Analysis was conducted to determine the factor structure of the SCS-SF in dementia and to further assess construct validity. Differences in self-compassion based on participant age, gender, dementia subtype and time since diagnosis were also analysed. The study findings, implications and future recommendations are discussed. Part Three: Appendices for the systematic literature review and empirical paper.
Keywords: Clinical psychology